EXPERIMENTAL STUDY OF ENERGY DISSIPATION IN A SINGLE STEP CONDITION OVER A BROAD CRESTED WEIR - Tanimu, Bashir; Usman, Aliyu Bamaiyi; Bello, Al-Amin Danladi; Abdullahi, Sulaiman Jamilu (FUDMA Journal of Sciences, 2021)
This research study the experimental performance of broad-crested weir with single-step by introducing U/S and D/S round-nose and analysing the parameters that have effect on the shape of the step and their effects on the flow characteristics and energy dissipation (E%) downstream (D/S) of the weir. Furthermore, empirical relations for E% and flow rate due to the influencing factors were derived. The results showed that the weir model with = 1.000 gives a higher E% in comparison with other weir models. Flow regimes were observed i.e nappe flow for small discharges, transition flow for intermediate discharges and skimming flow for higher discharges. Two model equations were obtained, the first to dteremine the flow rate over the weir models and the second relation to estimate E% in terms of, and Froude number. The model () can be used in the design of prototype weirs in terms of energy dissipation